1988
DOI: 10.1364/josaa.5.002106
|View full text |Cite
|
Sign up to set email alerts
|

Aging and human cone photopigments

Abstract: We used a noninvasive technique to investigate changes in photoreceptor function with aging in observers 13-69 years of age. This technique, steady-state color matching, provides estimates of the optical density of cone photopigments, the illuminance that bleaches half of the photopigment, and the ratio of the primaries required at moderate light levels. In normal human retinas, we found that the optical density for a 4-deg field is affected minimally by aging from the second through the seventh decades. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 15 publications
5
42
0
Order By: Relevance
“…28 There are only small individual differences across subjects, indicating well-regulated kinetics in normal subjects. Several methods have shown changes with normal aging in both the kinetics [26][27][28][29] and the optical density of cone photopigment in the centralmost fovea.…”
Section: B Changes With Aging and Diseasementioning
confidence: 95%
See 3 more Smart Citations
“…28 There are only small individual differences across subjects, indicating well-regulated kinetics in normal subjects. Several methods have shown changes with normal aging in both the kinetics [26][27][28][29] and the optical density of cone photopigment in the centralmost fovea.…”
Section: B Changes With Aging and Diseasementioning
confidence: 95%
“…28 There are only small individual differences across subjects, indicating well-regulated kinetics in normal subjects. Several methods have shown changes with normal aging in both the kinetics [26][27][28][29] and the optical density of cone photopigment in the centralmost fovea. 33,37,38 In retinal disease, this color matching technique has been able to reveal changes in optical density [39][40][41] and kinetics.…”
Section: B Changes With Aging and Diseasementioning
confidence: 95%
See 2 more Smart Citations
“…Previous studies have reported age-related decreases in photopigment OD based on reflection densitometry (Kilbride et al, 1986;Keunen et al, 1987;Coile & Baker, 1992) and color matching (Eisner et al, 1987;Elsner et al, 1988;Swanson & Fish, 1996). Because these aging studies have been conducted with trichromats, the photopigment OD of M-and L-cones may have been confounded.…”
Section: Introductionmentioning
confidence: 99%